Umur, Tingkat Pendidikan, Penghasilan Bruto, Moral Dan Kepatuhan Pembayaran Pajak - Isthi Wahyuning Tyas (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2015)
The issues discussed in this study was the influence of age, educational level, gross income and moral for the tax payment compliance. The purposes of the study are finding the empirical evidence on: (1) the effect of age on the taxpayer compliance of tax payments; (2) regarding the effect of education on adherence tax payments; (3) the effect of the gross income of the taxpayer compliance of tax payments; and (4) regarding the moral influence taxpayer to the tax payment compliance. This type of research is the quantitative study of causality. The population in this study is the individual taxpayer entrepreneur in Ciputra Mall. The selection of the sample with convenience sampling method. Types of data used is the data subject, and data sources used are the primary data. Data collection method used is by using a questionnaire distributed to 100 respondents. The analysis used is multiple regression analysis. The results showed that (1) age taxpayer has positive and significant effect on adherence to pay tax; (2) education taxpayer has positive and significant effect on adherence to pay tax; (3) gross income taxpayer has positive and significant effect on adherence to pay tax; and (4) moral taxpayer has positive and significant impact on adherence to pay taxes.